2017
DOI: 10.1039/c6ra25095e
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and experimental study of the antifreeze protein AFP752, trehalose and dimethyl sulfoxide cryoprotection mechanism: correlation with cryopreserved cell viability

Abstract: In this work the physico-chemical properties of selected cryoprotectants (antifreeze protein TrxA-AFP752, trehalose and dimethyl sulfoxide) were correlated with their impact on the constitution of ice and influence on frozen/thawed cell viability. The freezing processes and states of investigated materials solutions were described and explained from a fundamental point of view using ab-initio modelling (molecular dynamics, DFT), Raman spectroscopy, Differential Scanning Calorimetry and X-Ray Diffraction. For t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 37 publications
6
50
0
Order By: Relevance
“…First, we used the same gates in all experiments, and second, in all cases, we excluded cell debris more precisely (as compared to RSC Adv.) 3 . The same gating and the same style of debris exclusion is extremely important to correctly evaluate viability of freeze-thawed cells because many of these cells are more or less fragmented.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…First, we used the same gates in all experiments, and second, in all cases, we excluded cell debris more precisely (as compared to RSC Adv.) 3 . The same gating and the same style of debris exclusion is extremely important to correctly evaluate viability of freeze-thawed cells because many of these cells are more or less fragmented.…”
Section: Resultsmentioning
confidence: 99%
“…However, extensive damage occurs to a percentage of frozen and thawed cells and tissues. Though the freeze-thaw process can be greatly affected by the use of cryoprotective additives to improve cell viability 3 , 4 , the effects of freezing and cryoprotectants per se on the complex status of cell nuclei (and the genetic information contained therein) remain controversial 4 7 . Contradictory results in the literature have prevented a consensus on the fundamental question of the extent of DNA and chromatin fragmentation that occurs during freezing and thawing 8 – 11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryopreservation of cells plays an essential role in many areas [1][2][3][4][5]. The main difficulty in cryopreservation is that ice crystallization, which appears throughout the freezing process, can significantly damage the cells and cause the loss of viability after the cells are thawed [6].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have considered the impacts of low-dose radiation, given as a single dose or fractionated or prolonged over time, with regard to altering cancer progression or resolution as well as their impacts on the systemic immune system [23] .It was found that low-dose radiation increases cellular antioxidant activity; facilitates DNA damage repair; reduces malignant transformation and mutagenesis, and stimulates immune surveillance [24]. The cell nucleus and DNA are susceptible to several stressors[25, 26,27,28] and can be greatly harmed with relatively low doses of ionizing radiation [29,30]. As adverse effects of ionizing radiation on (cancer) cells are mainly mediated by fragmentation of nuclear chromatin via inserting double strand breaks (DSBs) into the DNA molecule [31].…”
Section: Discussionmentioning
confidence: 99%